Penguatan Capacity Building Berbasis Nilai-Nilai Pancasila di Lembaga Adat Desa Kayu Kebek, Kecamatan Tutur, Kabupaten Pasuruan - Listyaningsih Listyaningsih; Warsono Warsono; Raden Roro Nanik Setyawati; Maya Mustika Kartika Sari; Siti Maizul Habibah; Beti Indah Sari; Edy Suprianto (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Indigenous institutions have an important position in maintaining social order and local cultural identity in the midst of ongoing social change. This community service aims to strengthen the capacity of customary institutions in Kayu Kebek Village, Tutur District, Pasuruan Regency through a capacity building approach that is integrated with Pancasila values. Activities are carried out through participatory observation, institutional training, workshops on Pancasila values, and assistance in strengthening the organizational structure. The results of this activity show that the integration of Pancasila values in strengthening customary institutions can increase community participation, strengthen institutional identity, and create synergy between local and national values. This strengthening is an important foundation in creating socio-cultural resilience based on local wisdom.